The AIMSS Project: II. Dynamical-to-stellar mass ratios across the star cluster-galaxy divide - Forbes, Duncan A.; Huxor, Avon P. (Monthly notices of the Royal Astronomical Society, 2014)
Abstract. The previously clear division between small galaxies and massive star clusters is now occupied by objects called ultra-compact dwarfs (UCDs) and comp